Hydroxyapatite-Chitosan Composite Coating on TiAl Alloy Electrophoretic Deposition Method - Charlena Charlena; Irma Herawati Suparto; Chonny Damayanti (IPTEK Journal of Proceedings Series, 2017)
TiAl alloys is commonly used for bone implant applications because it has good biocompatibility. However, in long term usage of metal implants, metal release, which can harm the body, may occured. The metal release can be inhibited by hydroxyapatite-chitosan composite coating on the metal surface using Electrophoretic Deposition (EPD) method. EPD method carried out with 200 v for 40 and 60 minutes, to compare the impact of different interval time in producing the best product. The coated alloy was observed physically by SEM and showed that 60 minute-treatment produced better result. The XRD and FTIR analysis shows that the composite of hydroxyapatite-chitosan has successfully coated on TiAl alloy. The coated TiAl alloy also has low corrosion rate and could potentially be used as bone implants.